2018
DOI: 10.1371/journal.pone.0194416
|View full text |Cite
|
Sign up to set email alerts
|

Effect of developmental NMDAR antagonism with CGP 39551 on aspartame-induced hypothalamic and adrenal gene expression

Abstract: RationaleAspartame (L-aspartyl phenylalanine methyl ester) is a non-nutritive sweetener (NNS) approved for use in more than 6000 dietary products and pharmaceuticals consumed by the general public including adults and children, pregnant and nursing mothers. However a recent prospective study reported a doubling of the risk of being overweight amongst 1-year old children whose mothers consumed NNS-sweetened beverages daily during pregnancy. We have previously shown that chronic aspartame (ASP) exposure commenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 113 publications
(135 reference statements)
1
8
0
Order By: Relevance
“…Therefore, research on aspartame’s neurobehavioral effects has focused on monoamine neurotransmitter signaling. However, there is no consensus in the clinical or preclinical literature regarding aspartame’s effects on brain monoamine content or behaviors such as memory or depression ( 7 , 8 , 13 23 ). Similarly, despite reports of aspartame’s carcinogenic ( 24 , 25 ) and metabolic side effects ( 26 30 ), a consensus on these topics is lacking.…”
mentioning
confidence: 99%
“…Therefore, research on aspartame’s neurobehavioral effects has focused on monoamine neurotransmitter signaling. However, there is no consensus in the clinical or preclinical literature regarding aspartame’s effects on brain monoamine content or behaviors such as memory or depression ( 7 , 8 , 13 23 ). Similarly, despite reports of aspartame’s carcinogenic ( 24 , 25 ) and metabolic side effects ( 26 30 ), a consensus on these topics is lacking.…”
mentioning
confidence: 99%
“…Statistical analyses were performed using IBM SPSS statistics software version 20 (SPSS Inc., Chicago, IL) as previously described [27,35]. Data were presented as means ± SEM for body characteristics and Insulin Tolerance test (ITT).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was prepared from snap-frozen male and female adrenal and pancreatic tissue using Qiagen RNeasy Lipid Tissue Mini Kit Cat # 74804 (Qiagen, CA, USA) according to the manufacturer's instructions, and stored at − 80 o C, as described previously [35]. This method was slightly modified for pancreatic RNA extraction, according to De Lisle, 2014 [36].…”
Section: Rna Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have highlighted the essential roles of NMDAR in brain signal conduction and nerve function ( Yang et al, 2018 ; Zoodsma et al, 2020 ). Previous reports indicated that NMDAR is involved in various stress responses and plays a vital role in coordinating HPA axis activity ( Collison et al, 2018 ; Lin et al, 2019 ). Activation of NMDAR alters synaptic plasticity and evokes calcium spikes in the hypothalamic paraventricular nucleus (PVN) neurons ( Bains and Ferguson, 1999 ).…”
Section: Introductionmentioning
confidence: 99%